Formulation and Evaluation of Pharmaceutical Emulgel Co-loaded with Lornoxicam-Eugenol for Improved Analgesic and Anti-Inflammatory Effects - Prajapati, Ashish; Thagele, Rajkumari; Gupta, Mahesh Kumar; Kumar, Suraj; Rai, Rajat (Journal of Neonatal Surgery, 2025)
The present study focuses on the formulation and evaluation of a novel emulgel co-loaded with Lornoxicam and Eugenol, aiming to enhance topical analgesic and anti-inflammatory efficacy. Lornoxicam, a potent non-steroidal anti-inflammatory drug (NSAID), and Eugenol, a natural compound with known analgesic and anti-inflammatory properties, were incorporated into an emulgel system to overcome the limitations of oral administration, such as gastrointestinal side effects and poor patient compliance. The emulgel was formulated using Carbopol 940 as a gelling agent and evaluated for physicochemical parameters including pH, viscosity, spreadability, drug content, and stability. In vitro drug release studies demonstrated sustained and enhanced permeation profiles. The optimized formulation was further assessed through in vivo anti-inflammatory and analgesic models, such as carrageenan-induced paw edema and tail-flick tests in rats, which showed significant synergistic effects compared to formulations containing individual drugs. The results indicate that the co-loaded emulgel system offers a promising alternative for effective topical management of pain and inflammation with improved therapeutic outcomes and reduced systemic side effects.